THE PRINCIPALS’ STRESS IN BEDOUIN SCHOOLS IN ISRAEL DURING CORONA PANDEMIC - SLEIMAN ABURKAYEK (Annals of the University of Oradea: Economic Science, 2022)
The aim of this research is to explore the stress of the principals in Bedouin sector schools in Israel concerning remote teaching during COVID-19 pandemic. The interviews included eight (8) open–ended questions and were conducted with three (3) principals from different Bedouin schools in Negev concerning stress at work in the shadow of COVID-19. The main finding of this research is that the school principals in Bedouin were experiencing high levels of stress concerning distance teaching in the shadow of COVID-19 pandemic. The research findings also show that there is a lack of resources for remote learning among students in the Bedouin population, which was associated to the lack of the school principals’ control over teachers during the COVID-19, and was related to changes in the students’ behavior.